Coaching leadership and creative performance: A serial mediation model of psychological empowerment and constructive voice behavior - Hwang, Chan Young; Kang, Seung-Wan; Choi, Suk Bong (Frontiers in Psychology, 2023)
This study empirically analyzes the role of coaching leadership in enhancing an organization’s creative performance, discussing and evaluating important mediating paths of coaching leadership regarding creative performance. As a result of an empirical analysis based on survey data collected from 332 employees of Korean companies, this study first confirms that coaching leadership has a positive effect on both employees’ creative performance. We also found that psychological empowerment and constructive voice behavior positively mediated the relationship between coaching leadership and creative performance. Finally, the serial mediating effect of coaching leadership on creative performance was tested through psychological empowerment and constructive voice behavior and confirmed to have a positive effect. This study indicates the importance of leadership as a critical variable that promotes employees’ creative performance. In addition, by confirming the serial mediating role of psychological empowerment and constructive voice behavior, this study improves understanding of key mechanism in which coaching leadership leads to creative performance.